Writing Equation in Vertex Form Given Vertex and a Point Suppose we wanted to find the vertex and the standard form of a quadratic given a point and a vertex. Say that fireworks reach 100 feet after 10 seconds and it starts from the ground. We know 2 points on our parabola, 10,100 and 0,0. We use the vertex form of the equation y = a(x - h)2 + k y = a(x-10)2 + 100          fill in our vertex then fill in out point (0,0) for the x and y 0 = a(0-10)2 + 100 0 = a(100) + 100 100a = -100 a = -1 Then put the a into the original equation y = -1(x - 10)2 + 100 y = -1(x2 - 20x + 100) + 100 y = -x2 + 20x          which is the equation in standard form Suppose that we fired a rocket and it reached its vertex of 40 feet after 3 seconds. We also know that after 1 second it was at a height of 20. Write the equation of the line. Given that we have the vetex (3,40) and a point (1,20), we can solve the problem. y = a(x-h)2 + k y = a(x-3)2 + 40          fill in the vertex 20 = a(1-3)2 + 40         fill in the known point 20 = a(1-3)2 + 40 20 = 4a + 40 4a = -20 a = -5 Then fill that into the standard equation y = -5(x-3)2 + 40 y = -5(x2 - 6x + 9) + 40 y = -5x2 + 30x - 45 + 40 y = -5x2 + 30x - 5 We can see from the standard equation that the rocket was shot off from 5 feet below ground level. Fireworks reach a height of 50 feet after 10 seconds (10,50) (starting on the ground (0,0)). Write the equation of the paraobola y = a(x-h)2 + k 0 = a(x - 10)2 + 50 0 = 100a + 50 100a = -50 a = -1/2 y = -1/2(x - 10)2 + 50 y = -1/2(x2 - 20x + 100) + 50 y = -1/2x2 + 10x -40 + 40 y = -1/2x2 + 10x Given Vertex = {-1,-4} and a point on the graph is {0,-3) Write in Vertex form of the equation and Standard form y=a(x-h)2 + k y=a(x--1)2 - 4 y=a(x+1)2 - 4 -3=a(0+1)2 - 4 -3 = a - 4 a = 1 y = 1(x + 1)2 - 4 y = x2 + 2x + 1 - 4 y = x2 + 2x - 3 A rocket goes up from the ground and after 3 seconds it reaches its peak of 90 feet. We know vertex 3,90 and a point 0,0 y = a(x-h)2 + k 0 = a(0-3)2 + 90 0 = 9a + 90 9a = -90 a = -10 y = -10(x-3)2 + 90 y = -10(x2 - 6x + 9) + 90 y = -10x2 + 60x - 90 + 90 y = -10x2 + 60x |